Prestasi Belajar Siswa : Kompetensi Pedagogik Guru dan Motivasi Belajar Siswa - Roy Wahyuningsih (Jurnal Paedagogy, 2021)
This study aims; (1) to analyze the effect of teacher pedagogic competence on student achievement, (2) to analyze the effect of learning motivation on student achievement, (3) to analyze the effect of pedagogic competence and student motivation on student achievement. This research is a quantitative study using multiple linear regression.The population in this study were all students of XI TKJ, totaling 60 students. Researchers used a questionnaire in the form of google form as an instrument to facilitate data collection. From the results of multiple linear regression analysis, it can be concluded that (1) pedagogical competence has an effect on student achievement; (2) learning motivation affects student achievement, (3) pedagogical competence and student motivation affect student achievement.